Relationship Between Weight Status and Self-Image Mediated by Pubertal Timing and Athletic Competence: A Cohort Study With Taiwanese Adolescents - Kuo, Jen-Hao; Ubeda Herrera, Josue Jaru; Liu, Chia-Yi; Lee, Ting-Hsuan; Strong, Carol; Lin, Chung-Ying; Chang, Yun-Hsuan; Lin, Yi-Ching; Hsieh, Yi-Ping; Tsai, Meng-Che (Frontiers in Public Health, 2022)
Background Self-image reflects overall self-acceptance in developing adolescents. Using a representative cohort of Taiwanese youth, this study aims to explore the relationship between weight status, pubertal timing, athletic competence, and adolescent self-image. Methods Data come from the Taiwan Youth Project that comprised a longitudinal cohort of adolescents (N = 2690, 51% males, Mage = 13.3 ± 0.5 years) surveyed annually from seventh grade. Self-image was measured by perceived satisfaction with appearance and physique. Weight status was proxied by self-reported body mass index (BMI; kg/m2). Pubertal timing was defined using the Pubertal Developmental Scale, which mainly measured physical changes in puberty. Athletic competence was assessed by experiences with participation in competitive sports and self-perceived talent for sports. Linear regression analysis was applied to test for an association between BMI and self-image. In order to test for mediating roles of pubertal timing and athletic competence, Hayes' PROCESS macro on SPSS was conducted by applying 5,000 bootstrap resamples with 95% confidence intervals of the indirect effect. Results BMI was inversely associated with self-image in both males (β = -.074, [-.095, -.053]) and females (β = -.095, [-.122, -.069]). The boot strapped 95% confidence intervals indicated statistically significant mediating effects of pubertal timing (β = -.008, [-.015, -.001]) and athletic competence (β = -.006, [-.011, -.002]) in the link between BMI and self-image in females, whilst only athletic competence mediated this association (β = -.006, [-.009, -.002]) in males. Moreover, BMI at baseline were also associated with long-term self-image in males (β = -.037, [-.057, -.017]) and females (β = .132, [.073, .190]). Conclusions Understanding the mediating factors may help to enhance adolescents’ self-image by providing guidance on healthy weight and physical activity behaviors according to different stages of pubertal progression.